HUBUNGAN DEPRESI DENGAN INTERAKSI SOSIAL LANJUT USIA DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT - Rau, Nia Aprindah; Rompas, Sefti; Kallo, Vandri D (JURNAL KEPERAWATAN, 2017)
Abstract : The process of aging was a lifelong process that was not only starting from a certain time, but starting from the beginning of life. An increasing number of elderly followed by health problems faced due to the degenerative process. Due to the physical and psychological changes of the elderly,many of them were depressed which is one of the most mental illnesses that occur in the world. Social interaction wasinterplayamong individual relationshipswith one another with the result thatinfluenced, alter, or improve the behavior of other individuals or vice versa. The purpose of this research wasto knowing the Correlation between Depression with Social Interactions of the Elderly at the village of Upper Tombasian, District of West Kawangkoan. The Design of This Study used cross sectionalthat is the data which related to the independent variables and the dependent variable or risk or due to be collected in the same time. The sample was taking by using the purposive sampling technique with a total sample of 61 respondents. The results of the statistical testof Chi-Square with a confidence level of 95% (Î± = 0.05) and obtained p value = 0,003<0.05. The summary of this research was there is the correlation between Depressions with Social Interactions of the Elderly in the village of Upper Tombasian, District of WestKawangkoan. Keywords : Depression, Social Interaction, Elderly Abstrak: Proses menua merupakan proses sepanjang hidup yang tidak hanya dimulai dari suatu waktu tertentu, tetapi dimulai sejak permulaan kehidupan. Peningkatan jumlah lanjut usia diikuti dengan permasalahan kesehatan yang dihadapi karena proses degenetatif. Dikarenakan perubahan fisik maupun psikologis dari lansia banyak dari mereka mengalami depresi yang merupakan salah satu penyakit mental paling banyak yang terjadi didunia. Interaksi sosial merupakan hubunngan saling mempengaruhi antara individu satu dengan yang lainnya sehingga dapat mempengaruhi, mengubah, atau memperbaiki prilaku individu yang lain atau sebaliknya. Tujuan Penelitian mengetahui Hubungan Depresi dengan Interaksi Sosial pada Lanjut Usia di Desa Tombasian Atas Kecamatan Kawangkoan Barat. Desain Penelitian ini menggunakan cross sectional yaitu data yang menyangkut variabel bebas atau resiko dan variabel terikat atau akibat akan dikumpulkan dalam waktu yang bersamaan. Teknik pengambilan Sampel menggunakan teknik purposive sampling dengan jumlah sampel sebanyak 61 orang. Hasil uji statistic Chi-Square test dengan tingkat kepercayaan 95% (Î±=0,05) dan diperoleh p value 0,003 < 0,05. Simpulan yaitu terdapat Hubungan Depresi dengan Interaksi Sosial pada Lanjut Usia di Desa Tombasian Atas Kecamatan Kawangkoan Barat. Kata Kunci : Depresi, Interaksi Sosial, Lansia